Investigating the Performance of Hybrid Wind-Microturbine Generation System in Stand-Alone Environment - Singh, Bhanu Pratap (My University, 2014)
The energy demands increment, perishing resources of fossil fuels and growing pollution levels lead to the electricity generation using renewable sources such as wind, solar, geothermal, tidal etc. Further, these sources remarkably reduce pollution levels and climate changes. however, with renewable resources availability is affected by natural causes. Conventional sources like diesel, natural gas etc. shall be incorporated with the renewable energy sources to ensure the continuity in supply. in the proposed work, a hybrid generation system is presented which constitutes interfacing of microturbine generation and renewable energy system(wind power). A simulation model of the hybrid generation system is designed and its various characteristics are observed. From the developed model, it is observed that microturbine generation system acts as a back up generation system for wind energy conversion system and also supplies reactive power for asynchronous generator starter
M.E. (Power Systems)
Keywords: Microturbines; Hybrid generation; Power electronics interface; voltage regulator; Wind turbine